İşverenin eşit davranma borcu - Muzır, Esra (My University, 2020)
Toplumsal hayatta sıklıkla karşılaşılan sorunlardan biri işverenin aynı veya benzeri işiyapmakta olan işçileri arasında haklı ve makul sebebe dayanmaksızın ayrımcı davranıştabulunmasıdır. İşçi işveren ilişkisinde meydana gelebilecek olan eşit davranma borcuna aykırıdavranışların önlenmesi amacı ile eşit davranma borcuna aykırılık birtakım yasaldüzenlemelerle yaptırım altına alınmıştır. Tezimizde işverenin eşit davranma borcunun amacı,kapsamı, şartları ve iş sözleşmesinin kurulması, devamı ve sona ermesi aşamalarındakigörünüm şekilleri, aykırılığın ispatı ve eşit davranma borcuna aykırılık halinde işçininbaşvurabileceği hukuki, idari ve cezai yaptırımlar incelenmiştir.

One of the issues that is encountered frequently in social life is that the employerdiscriminates against one employee over another based on non-reasonable and justifiedreason who does same or similar work. In order to prevent acts contrary to the obligation ofequal treatment that may occur in the employee-employer relationship, the breach of theobligation of equal treatment has been penalised through a set of legal adjustments. In thisthesis, the purpose, scope, conditions of the obligation of equal treatment and theappearance of the employment contract at the stages of establishment, continuation andtermination, proof of breach and in the event of breach the employee's rights under legal,administrative and criminal penalties are examined.
Keywords: Civil law; İşverenin Eşit Davranma Borcu Obligation of equal treatment; Medeni hukuk